Trapped and resistant body: everyday practices of women in Taiwan in the context of intimate partner violence - Zhang, Luyue (Journal of family violence, 2021)
The extensive literature on intimate partner violence (IPV) against women has focused on the single actors of forces imposed on women. Little is known about the intertwined relationships among the roles of multiple participants in the context of IPV. This study used Michel de Certeau’s concepts of strategies, tactics, and space to explore the power struggle between female survivors and IPV perpetrators, family members, and institutions. This study used data collected in semi-structured interviews between 2016 and 2018 with 24 women (30 to 54 years of age) in Taiwan who experienced IPV from their male partners. Thematic analysis was used to identify and organize themes based on the concepts of strategies, tactics, and spatial actions. Three coders analyzed the data based on the conceptual framework, and inter-rater reliability was evaluated to ensure the quality of the results. Six themes were identified and grouped into two dimensions. Female Taiwanese survivors of IPV confronted not only the strategies of their male partners and families but also strategic mechanisms from the police and nongovernmental organizations. Female survivors found tactical opportunities to evade or resist everyday forms of strategic power. Understanding the quotidian experiences of female survivors has important implications for their protection and support to help them increase their safety and well-being when they are involved in an IPV relationship in particular, and spatial power structures in general.